Using TikTok as a Media to Enhancing Speaking Skills in English Foreign Language Classroom - Rangga Mega Putra (CV. Creative Tugu Pena, 2024)
The objective of this study was two fold: (1) to examine the speaking abilities of seventh-grade students at SMP Ma'arif NU 4 Darurrohmah through the use of TikTok video-based media, and (2) to assess the improvement in these abilities as a result of this intervention. This research employed Classroom Action Research (CAR) methodology, conducted in two cycles, each encompassing planning, action, observation, and reflection. Both quantitative and qualitative data were collected, with tests serving as the primary assessment instrument. The study population included all seventh-grade students at SMP Ma'arif NU 4 Darurrohmah, from which a purposive sample of 30 students from class 7.1 was selected. The findings indicated a significant enhancement in the students' speaking abilities regarding descriptive texts following the implementation of TikTok video-based media. Notably, students not only improved their vocabulary but also reported a more enjoyable learning experience. In the pre-test, 10 students (33%) achieved scores above 75. This number increased to 15 students (50%) in the post-test of Cycle 1, and further to 25 students (83%) in the post-test of Cycle 2. These results underscore a substantial improvement in the students' speaking capabilities. In conclusion, the integration of TikTok video-based media proved effective in enhancing the speaking abilities of students, particularly in the context of descriptive texts, thereby affirming the success of the research.